The Utility and Limitations of the Transfibular Approach in Ankle Trauma Surgery - Mustafa Yassin; Avraham Garti; Muhammad Khatib; Moshe Weisbrot; Uzi Ashkenazi; Edward Ram; Dror Robinson (Case Reports in Orthopedics)
The commonly used extensive approaches to the distal tibia include the posteromedial and anterolateral approaches. The current report describes several cases performed using this technique establishing a rationale and safe zone for performing a transfibular approach to the distal tibia. The advantages of such approach are the excellent visualization of the lateral tibia and the articular space. The utilization of this approach involves the risk of injury to the anterior tibial vessels and to the superficial peroneal nerve as well as a requirement for syndesmosis reconstruction. The recommendation is to utilize this approach in cases of severe comminution of the lateral tibia with a relatively intact medial tibia.